α-ZrP: A Highly Efficient Catalyst for Solvent-free Synthesis of Pyrimido[ 5',4':5,6]pyrido[2,3-d]pyrimidinetetraone and 4-Arylacridinedione Derivatives - Abdolmohammadi, Shahrzad (Letters in Organic Chemistry, 2014)
A solvent-free approach for the synthesis of a series of pyrimido[5',4':5,6]pyrido[2,3-d]pyrimidinetetraone and 4-arylacridinedione derivatives is described herein. These compounds having biological importance were prepared via a condensation reaction of aryl aldehydes, ammonium acetate and active methylene compounds including 1,3- dimethylbarbituric acid or dimedone under solvent-free conditions, using Zr(HPO4)2.H2O (α-ZrP) as an efficient catalyst. The reusability of catalyst and easier isolation of the products along with high yields of products are the advantages of this eco-friendly and versatile protocol.
Keywords: Zr(HPO4)2.H2O (α-ZrP)